Calculation of property diagram as a Zero-Phase Fraction line of auxiliary phase. (December 2016) - Kang, Youn-Bae; Chartrand, Patrice
Abstract: An approach to calculate various properties of solution is presented using CALPHAD phase diagram software. The properties include iso-bar, iso-activity, iso-activity coefficient, iso-sulfide capacity, iso-surface tension of various types of solutions such as liquid oxide or liquid alloy. Auxiliary phase(s) is introduced in order to set an equilibrium between a real solution and an auxiliary phase, where the property of the real solution is interesting. Gibbs energy of the auxiliary phase is set to yield a phase boundary between the real solution and the auxiliary phase, and the phase boundary becomes the iso-property line. The iso-property line is a phase boundary, therefore, it can be calculated as a Zero-Phase Fraction (ZPF) line of the auxiliary phase. This approach shows an easy way for calculating of the property diagram. The approach may be programmed into existing commercial CALPHAD software for the phase diagram calculation. Abstract : Highlights: Iso-property lines are automatically calculated using phase diagram software using CALPHAD method. The properties include partial pressure, activity, activity coefficient, sulfide capacity, and surface tension. Auxiliary phase is introduced in order to allow the calculation of the iso-property line.